Analysis of fracture resistance and surface characteristics of bioactive ceramic cluster filler and bulk fill fiber-reinforced composites in endodontically treated teeth - Hayati, Maulida; Natsir, Nurhayaty; Trilaksana, Aries Chandra (Brazilian Dental Science, 2026)
Objective: This study aimed to compare the mechanical, surface, and interfacial properties of a bioactive ceramic cluster filler composite (TMR-Z Fill 10) and a fiber-reinforced bulk-fill composite (EverX Posterior) in ETT, with intact teeth serving as controls. Material and Methods: Forty-five extracted maxillary premolars were divided into three groups (n = 15): intact teeth, TMR-Z Fill 10 restorations, and EverX Posterior restorations. Fracture resistance was measured using a universal testing machine. Surface roughness and morphology were analyzed by atomic force microscopy (AFM). Interface gaps and elemental composition were evaluated using scanning electron microscopy and energy-dispersive spectroscopy (SEMEDS). Mineralization profiles were determined with Fourier-transform infrared spectroscopy (FTIR). Data were analyzed using one-way ANOVA and Post-Hoc Tukey HSD (p < 0.05). Results: Fracture resistance of TMR-Z Fill 10 (1760.86 ± 330.31 N) was comparable to intact teeth (1785.84 ± 367.25 N) and significantly higher than EverX Posterior (1491.96 ± 275.91 N; p < 0.05). AFM revealed smoother surfaces on composites than on enamel, with TMR-Z Fill 10 showing greater uniformity. SEM demonstrated narrower gaps in EverX (3.60 ± 0.43 µm) than in TMR-Z Fill 10 (8.40 ± 0.82 µm). EDS confirmed bioactive ion release from both composites, while FTIR indicated fluoride-mediated remineralization in TMR-Z Fill 10 but weaker carbonate stability in EverX. Conclusion: TMR-Z Fill 10 preserved fracture resistance and supported remineralization, whereas EverX Posterior provided superior marginal adaptation. Neither material fully replicated intact teeth, but each exhibited distinct advantages for restoring ETT.KEYWORDSBioactive composite; Endodontically treated teeth; Fiber-reinforced composite; Fracture resistance; Interface gap